Exciton absorption spectrum of Cs4PbCl6 thin films - Yunakova, O. N.; Miloslavsky, V. K.; Kovalenko, E. N.; Kovalenko, V. V. (Institute for Single Crystals, 2015)
The absorption spectrum of thin films Cs4PbCl6 is studied in the spectral range of 2-6 eV within the temperature interval 90-500K. Localization of exciton excitations in the sublattice of the compound containing Pb2+ ions is established. Excitons related to excitons of the intermediate bond and are two-dimensional nature
Keywords: thin films; absorption spectra; exitons